Study of the wear and rolling contact fatigue of class B wheel against the R350HT and R260 rail steels using the twin-disc wear simulator - Siyasiya, Charles Witness (University of Pretoria, 2024)
Thesis (PhD (Metallurgical Engineering))--University of Pretoria, 2023.